A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean - Pawson, David L. (Zootaxa, 2018)
Astrophiura caroleae, new species, is described from off Curacao in the southern Caribbean, and from the western Gulf of Mexico, in depths of 244 to 434 meters. This new species, the first in the genus Astrophiura to be described from the Atlantic Ocean, has a distinctive combination of characters, including regularly arranged primary plates, large radial shields whose radial edges are in contact for their entire visible length, and prominent tubercles on central and radial plates. The mottled reddish coloration of the dorsal surface of this species usually contrasts with the color of the substratum, rendering it readily visible in situ, despite its disc diameter of less than 10 mm. Like its congeners, A. caroleae is gonochoric, the gonads of females containing conspicuous masses of bright orange eggs that are approximately 165 µm in diameter. DNA Barcoding data are provided for this new species, these are the first for Astrophiura.